2019
DOI: 10.1111/sms.13499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperhydration on the pharmacokinetics and detection of orally administered budesonide in doping control analysis

Abstract: The aim of the present study was to investigate if hyperhydration could influence the excretion and subsequent detection of budesonide (BDS) and its main metabolites (6β‐hydroxy‐budesonide and 16α‐hydroxy‐prednisolone) during doping control analysis by leading to concentrations below the WADA reporting level (30 ng/mL). The influence of hyperhydration on the plasma and urinary pharmacokinetic (PK) profiles of BDS and metabolites was also examined. Seven healthy physically active non‐smoking Caucasian males par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Here, the modification of the currently enforced reporting level from 30 to 40 ng/ml was suggested, which would be applicable also in case of hyperhydration scenarios, which were shown to exert no effect on the pharmacokinetics of orally administered budesonide (9 mg). The observed reduced urinary concentrations (as potentially provoked by athletes to decrease urinary concentrations of a banned substance below the reporting level) were shown to be adequately compensated by specific gravity adjustments, if required 164 …”
Section: Corticoids and Cannabinoidsmentioning
confidence: 97%
“…Here, the modification of the currently enforced reporting level from 30 to 40 ng/ml was suggested, which would be applicable also in case of hyperhydration scenarios, which were shown to exert no effect on the pharmacokinetics of orally administered budesonide (9 mg). The observed reduced urinary concentrations (as potentially provoked by athletes to decrease urinary concentrations of a banned substance below the reporting level) were shown to be adequately compensated by specific gravity adjustments, if required 164 …”
Section: Corticoids and Cannabinoidsmentioning
confidence: 97%
“…The initial results were corroborated and expanded on by numerous studies published thereafter which further evidenced the systemic distribution by measuring not only urinary but also plasma concentrations of the drugs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] As a consequence, the status of local injections in the WADA Prohibited List needed to be re-evaluated. 5-7 13 19 20 The need for reliable and practical guidance for physicians treating athletes with GCs has also been recognised by WADA since the first inclusion of GCs on the Prohibited List.…”
Section: Reviewmentioning
confidence: 99%
“…However, different studies have shown the need to establish compound-specific RLs given the diversity of administration routes and doses, as well as pharmacokinetic and pharmacodynamic properties between the different GCs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The ideal RL should not produce AAFs after permitted administrations or negative results after prohibited use. When testing athletes, the potential for AAFs after permitted administrations for therapeutic purposes have to be precluded, therefore the RL must be based on concentrations obtained after permitted administrations.…”
Section: Establishing Improved Urinary Rls For Gc Usementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, a criterion to distinguish allowed and prohibited administration is needed in antidoping controls, in order to ensure safe treatments by allowed routes of administration and to detect the use of prohibited routes of administration during competitions. A general urinary reporting level of 30 ng/ml was established by WADA to perform the discrimination 12 ; however, different studies have shown that the use of a single criterion is not suitable for all GCs given the diversity of administration routes, doses and pharmacokinetic and pharmacodynamic properties of the compounds of the group 13–23 …”
Section: Introductionmentioning
confidence: 99%